Advertising expenditures in Brazil and its connection with the international economy - Pesavento, Fábio; Marques, André (REBRAE, 2016)
The strong performance of the Brazilian economy during the 2000s allows the expansion of various sectors, including the advertising market, associated with the growth of the domestic market and the intensification of trade relations with other countries. The main objective of this study is to test the Relative Constancy Principle (RCP) in the context of greater integration with international economy, controlling for several factors that may exhibit some influence on the performance of the advertising market. We adopt a panel data of two periods for 49 countries and estimate a linear fixed effects model with dummies, controlling for the heterogeneity and unobserved factors of the countries. The results suggest that the advertising market of China, the United States and India have significant patterns above the average. The study does not support the RCP, yet they identify important regularities in those countries in relation to the advertising market. The level of activity and international reserves have a significant effect on the advertising market in countries; the higher the share of industry and services (urbanization), the higher the expenses on advertising; the inflation rate is nonlinearly related to the advertising market performance; the economic freedom index and the presence of Generations X and Y are associated with a reduction in advertising expenditure.